Qualitative GIS a mixed methods approach - Cope, Meghan; Elwood, Sarah (SAGE, 2009)
Geographic information systems (GIS) are an essential tool for analyzing and representing quantitative spatial data. This title explains the recent integration of qualitative research with GIS.